HUBUNGAN ANTARA CITRA TUBUH DAN TINGKAT HARGA DIRI PADA SISWI SMA FONS VITAE I TAHUN AJARAN 2019/2020 - Pangestian, Michael; Prihadi, Prihadi; Agus, Dharmady (Sriwijaya Journal of Medicine, 2020)
. Many teenagers who experience dissatisfaction with changes in body shape. Mismatched the reality of actual body shape and ideal body image perception triggers negative body image perception which can cause a decrease in self-esteem. In terms of gender, women's self-esteem levels tend to be lower compared to men. This study was an observational analytic study with a cross-sectional approach, taken at Fons Vitae I Senior High School with stratified random sampling. The body image was measured by using Body Shape Questionnaire-34 (BSQ-34) and self-esteem was measured by using Rosenberg Self Esteem Scale (RSES) questionnaire. Data are analyzed using chi-square. The total respondents were 109 female students. In univariate analysis there were 13.8% female students who had dissatisfaction with her body image and 86.2% female students who had satisfaction with her body image. Female students with low self-esteem were 19.3% and high self-esteem were 80.7%. The bivariate analysis shows that there is a significant association between body image and the level of self-esteem among Senior High School female students at Fons Vitae I (p = 0.039) with OR = 3.511. There is a significant association between body image and level of self-esteem.